Understanding the Effects of Ethylene Glycol-Assisted Biomass Fractionation Parameters on Lignin Characteristics Using a Full Factorial Design and Computational Modeling - Yu, Osbert; Yoo, Chang Geun; Kim, Chang Soo; Kim, Kwang Ho (ACS Publications, 2019)
Contributing to recent lignin valorization efforts, this study uses an integrative approach to explore the effects of fractionation parameters on lignin characteristics. The following reaction parameters are explored: water content of the water-organic solvent mixture, reaction temperature, and sulfuric acid content. Ethylene glycol (EG) was selected as the fractionation solvent because of its promising lignin solubility and extractability. This study takes a novel approach in conducting EG-assisted biomass fractionation; instead of removing lignin from the biomass, lignin was extracted and characterized. Lignin characteristics involving recovery and linkages were analyzed. A maximum of 27 wt % lignin recovery was achieved at a low water content (25%) and high reaction temperature (180 degrees C) in the presence of sulfuric acid (1 wt %). From NMR analysis, aryl-ether linkages, which are important to preserve for lignin valorization, were decomposed as a result of relatively high temperature and the presence of sulfuric acid. Statistical analysis showed that all individual parameters and their interactions had significant effects on lignin recovery. Computational analysis revealed that hydrogen bonding between the EG and lignin macromolecules greatly decreased with an increasing amount of water.